SOSIALISASI KOTAK BERSALIN DALAM UPAYA PENCEGAHAN PENULARAN INFEKSI COVID-19 DI KECAMATAN KOTO TANGAH - Hamidatul Yuni; Suci Maisyarah Nasution; Siti Nurhasanah (BULETIN ILMIAH NAGARI MEMBANGUN, 2020)
Most (77%) urban villages in Padang City still have positive cases of COVID-19 and the most are in Koto Tangah District. Prevention and mitigation measures are the key to implementation in health services. During the pandemic, the Public Health Care (PHC) continued to provide services to pregnant, childbirth and postpartum mothers. However, the transmission of COVID-19 to medical personnel and paramedics is getting higher in Indonesia, until July 2020 there were 1.2% of cases. For this reason, it is necessary to ensure that transmission prevention measures are carried out properly. The purpose of this activity is to socialize the “Delivery Chamber” to health workers at the PHC and the Midwives Independent Practice in Koto Tangah District. The method used in this activity is socialization. The outreach activities began with the construction of “Delivery Chamber” and giving them to several PHC and a midwife's independent practice site as a pilot for other health service centers. In addition, there is also a tutorial for making a Delivery Chamber which will be uploaded to Youtube as a virtual socialization medium. According to Aulia, video tutorials on Youtube have an influence on behavior and level of knowledge. The results of this activity were the delivery of Delivery Chamber to the Lubuk Buaya PHC, Anak Air PHC, Air Dingin PHC and Midwife Mariani. It is hoped that health service managers who provide childbirth services during the Covid-19 pandemic to provide a Delivery Chamber and follow the procedures for its use.